DETERMINATION OF THE FLOW OF INTERNAL AND EXTERNAL STAKEHOLDERS ON THE DEVELOPMENT OF THE ENTERPRISE - VLASENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Modern enterprise management systems can be effective only when adapted to the dynamics of the external and internal business environment and ensure timely changes of all processes for implementing new projects that use new opportunities or minimize threats and risks. One of the postulates of the concept of enterprise development is a balanced accounting of the interests and expectations of the organization’s stakeholders during the implementation of activities. Therefore, it is necessary to formalize the functions and responsibilities regarding communication with interested parties, gathering information, and prioritizing the needs of stakeholders. Interaction with interested parties should not be a one-time procedure but a continuous process accompanying the planning, implementation, and reporting stages. Evidently, even in companies that do not follow these principles in their strategies, there are interaction mechanisms with stakeholders. Stakeholder identification is often an underappreciated aspect of strategic sustainability planning and involves identifying internal and external stakeholders. Company managers must understand which stakeholders can influence its activities and how interested they are in its prosperity. This step allows you to identify the primary group of stakeholders whose interests should be prioritized and, therefore, should be involved in the decision-making processes for the enterprise. During the development of the company’s strategy, it is worth getting acquainted with their opinion, allowing participating in the discussion of management issues. Optimum simultaneous interaction with all stakeholders is quite complex and problematic because relations between stakeholders are often difficult to describe quantitatively - they are non-linear relationships simultaneously in network interaction with other network agents. Finding the optimal balance of satisfying stakeholders’ interests will allow the company to develop an optimal behavior plan. The results of the effective operation of the mechanism of managing relationships with stakeholders are expressed both in economic consequences - an increase in business value, optimization of income, expenses, and return on investment, and in results that determine the success of enterprises in the future - brand development, increasing the moral responsibility of employees, improving the quality of personnel, which is employed, the development of efficient logistics, increasing the sustainability of the business through the best risk management.